Hollywood or history? : an inquiry-based strategy for using television shows to teach issue-centered curriculum - Nance, Starlynn R. (Hollywood or history, 2022)
"Teaching with film is not a new approach in the social studies classroom. Different publications, such as Hollywood or History, have bridged the gap with challenges attached to using historical film and engage students through inquiry, not entertainment. To continue with the Hollywood or History strategy, this text uses television shows (sitcoms) to brings issue-centered curriculum to middle and high school classrooms. By exploring issues in specific episodes, students can learn the history behind an issue, relate it to their lives, and develop an informed decision associated with the issue. The College, Career, and Civic Life (C3) framework is an integral part to the exploration of issue-centered curriculum. In each chapter, the students will work through the four dimensions and develop critical thinking, reading, and writing skills. My hope is that this text can play a small role in walking practicing teachers through the C3 framework while allowing students to learn about issues that affect society and the communities they live"--